Racialised capitalism, decoloniality and the university: an exploration of the colour line and colonial unreason in higher education - Tegama, Natalie (Frontiers in Sociology, 2023)
Over the last decade, there has been an increase in calls to address important questions on race and decolonisation within the university, administratively, pedagogically, and socially. This paper investigates the relationship between the university, the coloniser and the colonised during the colonial era and afterlife. With the aim to demonstrate that the university has across disciplines made central the act of abstraction and theorisation in a way that shears theoretical principles from the historical contexts they emerge from. Distancing them from the purposes, people and interests they were meant to serve. As well as the populations they were meant to dispossess and disempower. The paper provides a conceptual framework for deconstructive analysis of the university’s pedagogical operations and societal function with the view to elucidate on the university’s colonial and racial blind spots. Notably with a reliance on disciplinary narratives from development, international relations, and international law to offer tentative answers to questions of decolonial praxis, the decolonial scholar and coloniality in the contemporary university.